2011
DOI: 10.1007/s10064-011-0398-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and the environmental acceptability of the natural stone quarrying waste rocks

Abstract: The paper summarises the results of a study by the Geological Survey of Finland on the potential use of waste rocks from natural stone quarry production. Petrographic, chemical, mechanical and physical tests were undertaken on granite, rapakivi granite, migmatite, syenite, diorite, gabbro, anorthosite gabbro, schist and soapstone from 33 dimension stone quarries in Finland. The results indicate the waste rocks of Finnish natural stone quarries can generally be considered environmentally sound with potential us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Delgado et al (2006) carried out a study on the environmental impact and showed that the granite fines do not constitute a significant hazard to the quality of natural waters. Luodes et al (2012) performed experimental work on granite, rapakivi granite, migmatite, syenite, diorite, gabbro, anorthosite gabbro, schist and soapstone, and showed that the waste rocks of Finnish natural stone quarries can generally be considered environmentally sound with potential uses in other industries.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Delgado et al (2006) carried out a study on the environmental impact and showed that the granite fines do not constitute a significant hazard to the quality of natural waters. Luodes et al (2012) performed experimental work on granite, rapakivi granite, migmatite, syenite, diorite, gabbro, anorthosite gabbro, schist and soapstone, and showed that the waste rocks of Finnish natural stone quarries can generally be considered environmentally sound with potential uses in other industries.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In the 2010s, a Newco (Carrara Marble Way srl, which groups 40 Carrara and Massa quarry company) decided to invest in EW management and recovery, creating a complete production line to exploit EW (from the best to the poorest quality). The starting point to evaluate the best potential applications for marble waste (both coarse and fine fractions) was to investigate different research dealing with the recovery of limestone and marble waste [74][75][76][77][78][79], including also the residual sludge produced during drilling activity and in processing plants [26,[80][81][82][83][84].…”
Section: Extractive Waste Management and Recoverymentioning
confidence: 99%
“…In the 10s of the XX century a Newco (Carrara Marble Way srl, which groups 40 Carrara and Massa quarry company) decided to invest in EW management and recovery, creating a complete production-line to exploit EW (from the best to the poorest quality). The starting point to evaluate the best potential applications for marble waste (both coarse and fine fractions) was to investigate different researches dealing with the recovery of limestone and marble waste [70][71][72][73][74][75], including also residual sludge produced during drilling activity and in working plants [24,[76][77][78][79][80].…”
Section: Extractive Waste Management and Recoverymentioning
confidence: 99%